Exploring Differences in the Role of Hospitalization on Weight Gain Based on Treatment Type From Randomized Clinical Trials for Adolescent Anorexia Nervosa - Datta, Nandini; Matheson, Brittany E.; Le Grange, Daniel; Brandt, Harry A.; Woodside, Blake; Halmi, Katherine A.; Wilfley, Denise E.; Lock, James D. (Frontiers in Psychiatry, 2020)
Background: This study explores the impact of weight gain during medical stabilization hospitalization on weight outcomes between three outpatient treatments for adolescent anorexia nervosa (AN): Adolescent Focused Therapy (AFT), Systemic Family Therapy (SyFT), and Family Based Treatment (FBT). Methods: A secondary analysis of weight gain data (N= 215) of adolescents (12-18 years) meeting DSM-IV criteria for AN (exclusive of amenorrhea criteria) who participated in two randomized clinical trials (RCTs) was conducted. Main outcomes examined were changes in weight restoration (>94% expected body weight or EBW) and differences in weight change attributable to hospital weight gain. Results: Weight gain resulting from hospitalizations did not substantially change weight recovery rates. Hospital weight gain contributed most to overall treatment weight gain in AFT compared to FBT and SyFT. Conclusion: Brief medical stabilization weight gain does not contribute substantially to weight recovery in adolescents with AN who participated in RCTs.